Prediksi Kebangkrutan pada PT Trikomsel Oke Tbk dengan Menggunakan Metode Altman Z-Score Modifikasi Periode 2012-2018 - Benny Barnas; Alfia Aprianti Kusuma Wardhani; Ine Mayasari (Indonesian Journal of Economics and Management, 2021)
The purpose of this research was to determine how to predict bankruptcy in PT Trikomsel Oke Tbk period 2012-2018. The method of this research was used descriptive research with quantitative approach. This research uses secondary data in the form of financial statements of PT Trikomsel Oke Tbk obtained from the company's official website in the period 2012-2018. The data analysis technique was used by Altman Z-Score Modification method. That method use four variable ratios to predicting bankruptcy, is Working Capital to Total Assets (X1), Retained Profit to Total Assets (X2), EBIT to Total Assets (X3), and Equity Book Value to Debt Book Value (X4). After the calculations in this research showed that PT. Trikomsel Oke Tbk. in 2012 to 2014 was in a safe area. Meanwhile, in 2015 to 2016 in a potential financial distress condition. Then in 2017 in a safe area and in 2018 in a potentially financial distress condition.